Investigating the Influence of Classroom Leadership Preferences on the Use of Technology: A Survey of Korean University Learners - Andrew Schenck (Ali Khorsandi Taskoh, 2023)
Although there are several studies which explore learner variation, little research has been conducted to investigate how different preferences for classroom leadership are linked to the use of technology. Fifty-seven Korean university students were given two surveys to examine preferences for both classroom leadership and the use of technology. After collecting responses, data was then compared using the non-parametric Spearman Rho formula for Likert-scale data. Results revealed distinctly different perspectives on technology, which appeared to be influenced by learner preferences for either autocratic or transformational leadership. Whereas learners with autocratic leadership preferences favored using technology to make knowledge transmission easier, learners with democratic or transformational leadership preferences favored the individualistic use of technology for knowledge creation and discovery. In addition to this distinction, leadership preferences also appeared to impact expectations for communication. Whereas learners who preferred autocratic leadership styles desired using technology to connect with other students, learners who preferred democratic-transformational and transformational leadership also desired close connections with teachers via technology, reflecting expectations for more egalitarian social relationships.